Penguatan Budaya Melayu di TVRI Riau Melalui Drama Televisi - Evizariza; M Kafrawi (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2023)
Television is a medium that can be used to disseminate information and entertainment. The development of increasingly sophisticated technology with various kinds of programs requires creative thinking so that television stations are not left behind by their audience. One of the superior programs that can be created is television dramas by incorporating local cultural values. By collaborating with TVRI Riau, Malay cultural values can be combined in a creative work, namely television drama.